1977
DOI: 10.1136/adc.52.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous fits after convulsions with fever.

Abstract: SUMMARY 112 of an original sample of 134 children with febrile convulsions were reviewed between 8 years and 9 years 10 months after their initial attack. 17 % of those followed up had had at least one spontaneous fit. A significant correlation was found with perinatal abnormalities. 12 % had continuing recurrent fits. Persisting grand mal occurred most commonly in lower social class children who had had perinatal abnormalities and continued to have long-term neurological disorders. Psychomotor epilepsy correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1978
1978
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 17 publications
(14 reference statements)
1
6
1
Order By: Relevance
“…Falconer et al (1964Falconer et al ( ,1968Falconer et al ( ,197 1,1974Falconer et al ( ,1976 first suggested that prolonged febrile convulsions in infancy or early childhood lead to development of temporal lobe epilepsy (TLE). Subsequent studies (Ounsted et al, 1966;Ounsted, 1967;Tsuboi and Endo, 1977a;Wallace, 1977;Nelson and Ellenberg, 1978;Rasmussen, 1979;Annegers et al, 1979Annegers et al, , 1987Lee et al, 1981;Schmidt et al, 1985;Ounsted et al, 1987;Rocca et al, 1987) reported conflicting results, perhaps because of variable methods of ascertainment or different study populations. Among patients with intractable TLE studied with a view to surgical treatment, 9-50% have a history of febrile convulsions (Paillas, 1958;Green, 1967;Jensen, 1976;Lindsay et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Falconer et al (1964Falconer et al ( ,1968Falconer et al ( ,197 1,1974Falconer et al ( ,1976 first suggested that prolonged febrile convulsions in infancy or early childhood lead to development of temporal lobe epilepsy (TLE). Subsequent studies (Ounsted et al, 1966;Ounsted, 1967;Tsuboi and Endo, 1977a;Wallace, 1977;Nelson and Ellenberg, 1978;Rasmussen, 1979;Annegers et al, 1979Annegers et al, , 1987Lee et al, 1981;Schmidt et al, 1985;Ounsted et al, 1987;Rocca et al, 1987) reported conflicting results, perhaps because of variable methods of ascertainment or different study populations. Among patients with intractable TLE studied with a view to surgical treatment, 9-50% have a history of febrile convulsions (Paillas, 1958;Green, 1967;Jensen, 1976;Lindsay et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Modern prospective studies failed to demonstrate a strong relationship between early febrile seizures and the later development of nonfebrile seizures of any type [24-271. Retrospective studies among patients with scalp EEG or clinical evidence of temporal lobe epilepsy also showed a low association of febrile seizures or childhood seizures with the subsequent development of chronic epilepsy [13, 161. Other retrospective studies that examined patients referred for neurosurgical management of CPSs found between 11 and 38% of patients with antecedent febrile seizures [23,[28][29][30].…”
Section: Etiologicul Fuctovsmentioning
confidence: 99%
“…It should be noted that studies of short, generalized, febrile seizures in healthy children over a year of age have shown a similar low prevalence of later epilepsy and a similarly poor ability to predict which few children will become epileptic (Lennox-Buchthal 1973, Nelson and Ellenberg 1976, Wallace 1977.…”
Section: Discussionmentioning
confidence: 99%